Comparison of the efficacy of mFOLFOX-6 and mDCF regimens in the treatment of metastatic gastric cancer: a multicenter retrospective study - Karhan, Ogur; Ileri, Serdar; Urakci, Zuhat; Sezgin, Yasin; Yildirim, Umit; Unlu, Beyza; Tunc, Sezai (Sage Publications Ltd, 2025)
Background: Metastatic gastric cancer (GC) and gastroesophageal junction (GEJ) cancer are associated with a poor prognosis. Recent advancements in treatment have incorporated trastuzumab, anti-PD-1 agents, and anti-claudin therapies alongside chemotherapy (ChT), significantly improving outcomes. Contemporary studies predominantly employ doublet ChT as the backbone for these regimens, although historically triplet ChT regimens have been favored, particularly in younger patients requiring rapid tumor shrinkage.Objective: The aim of this study was to compare the efficacy of mFOLFOX-6 and mDCF regimens in the treatment of advanced GC and GEJ adenocarcinoma.Design: This was a retrospective multicenter study.Methods: Patient data were obtained from the databases of 25 hospitals across Turkey. Demographic and clinicopathological characteristics were documented. Overall survival (OS) and progression-free survival (PFS) were analyzed using the Kaplan-Meier method, and group discrepancies were assessed with log-rank test.Results: A total of 493 patients were included in the analysis, with similar baseline characteristics between the two groups. The objective response rate was 36.3% in the mDCF group and 38% in the mFOLFOX-6 group (p = 0.7). The median PFS was 6 months for mDCF and 7 months for mFOLFOX-6 (p = 0.2), while the median OS was 12 months for mDCF and 11 months for mFOLFOX-6 (p = 0.4). Grade 3-4 neutropenia occurred in 27.6% of patients treated with mDCF versus 17.8% with mFOLFOX-6 (p = 0.01). Likewise, grade 3-4 anemia was more frequent in the mDCF group (9.5%) compared to the mFOLFOX-6 group (4.8%; p = 0.04).Conclusion: Modified FOLFOX-6 demonstrated comparable efficacy to mDCF in the treatment of advanced GC and GEJ adenocarcinoma. Moreover, mFOLFOX-6 was associated with a lower incidence of hematological adverse effects.
Keywords: chemotherapy; gastric cancer; metastasis; quality of life; survivorship; toxicity management